Mitochondrial abnormalities in Parkinson's disease and Alzheimer's disease: can mitochondria be targeted therapeutically? - Macdonald, Ruby; Barnes, Katy; Hastings, Christopher; Mortiboys, Heather (Biochemical Society transactions, 2018)
Mitochondrial abnormalities have been identified as a central mechanism in multiple neurodegenerative diseases and, therefore, the mitochondria have been explored as a therapeutic target. This review will focus on the evidence for mitochondrial abnormalities in the two most common neurodegenerative diseases, Parkinson's disease and Alzheimer's disease. In addition, we discuss the main strategies which have been explored in these diseases to target the mitochondria for therapeutic purposes, focusing on mitochondrially targeted antioxidants, peptides, modulators of mitochondrial dynamics and phenotypic screening outcomes.